Letter from the editor - Díez-Martín, Francisco (Journal of Management and Business Education, 2019)
this letter introduces the issue 3 (2019) of the Journal of Management and Business Education. the issue consists of five works related to: styles and student learning strategies; bachelor´s dissertation at the schools of economics and business; teachers and students’ committed with e-learning; validation of scales when implementing project-based learning; and webinar, a new global tool to promote deep learning in the classroom. In addition, the collaboration is appreciated to all those who have made possible the publication of this number.